The Influence of Competency and Spiritual Intelligence on The Performance of PT Employees in Bank NTB Syariah Head Office - Ambarwati, Rini; Atmayanti, Tati; Hayati, Sirrul (UIN Mataram, 2024)
The growth of the sharia banking industry in Indonesia is increasing, so it requires superior and professional quality human resources. The reality of fraud by employees at financial institutions such as Bank NTB Syariah certainly causes losses for the Company. Therefore, the urgency of this research is to focus on the influence of competence and spiritual intelligence on the performance of Bank NTB Syariah Head Office employees. This research uses a quantitative approach and the type of research isassociative causality. The total population was 271 respondents, and the sampling technique was quota sampling technique with the Slovin formula and the sample size was 73 respondents. The data collection technique uses questionnaires and documentation methods. The data analysis technique uses Multiple Linear Regression analysis using the SPSS version 24 application. The findings from this research show that there is a positive influence between the competency variable (X1) on the employee performance variable (Y). From a theoretical perspective, these findings show that competence can improve employee performance. This means that competency refers to the ability and behavior of employees in carrying out their duties and responsibilities and is able to improve their performance in their work. There is a positive influence of the spiritual intelligence variable (X2) on employee performance (Y). This means showing that spiritual intelligence is able to improve employee performance. This means that spiritual intelligence which is formed by honesty, flexible attitudes, quality of vision and values ??for self-development is able to improve employee performance in their work.